A geometallurgical study of an ore deposit in South–Western Mali - Zaouder, Abdourhamane Toure (University of Mines and Technology, 2018)
Geometallurgy provides a platform for cross-functional teamwork between geology and metallurgy, providing better inputs to mine planning and strategic decision making. Understanding variability in the orebody enables optimum operational designs and extraction methods that maximize value recovery. This research focused on the geometallurgical study of samples from seven potential orebodies in south-western Mali namely Fresh 01, Trans 01, Trans 02, Lower SAP 01, Lower SAP 02, Upper SAP 01 and Upper SAP 02. The study was conducted using X-ray Diffraction (XRD), fire assay/Atomic Absorption Spectrophotometry (AAS)/Inductively Coupled Plasma (ICP) for elemental analysis, Bond work index, abrasion analysis, gravity concentration and cyanide gold extraction with and without carbon. The gold assays were in the range of 0.36 g/t to 2.77 g/t with Fresh 01 being the lowest and Lower SAP 02 as the highest. The major gangue minerals observed include quartz, dolomite and montmorillonite. The work indices (BWi) of the ore types ranged from 5.6 to 13.3 kWh/t and abrasion (Ai) ore parameter ranged from 0.4 to 1.8. Sample Trans 02 gave the lowest grindability values. Gravity concentration gave concentrate grades between 5.3 g/t to 66.5 g/t and recoveries between 22% and 46%. Gold extraction by cyanide leaching was between 90% and 97%. Increasing cyanide concentration from 250 ppm to 500 ppm did not result in increased gold extraction. Overall gold recoveries were between 92% and 98%. Lime consumption was in the range of 1.5 – 3.5 kg/t (1.3 – 2.7 kg/t calcium oxide equivalent). Cyanide consumption was between 0.19 kg/t and 0.28 kg/t when concentration was maintained at 250 ppm. The geometallurgical model shows that the best blend had a grade of 2.09 g/t, Bond work index of 10.0 kWh/t and recovery of 97.8%
x, 89p; ill.
Keywords: Ore deposits; Extractive industry; Mine design; Mine planning; Geology